A low-cost inertia-based chassis dynamometer for performance evaluation of two-wheeler CVT vehicles - Guni, Abiral; Shakya, Prajwal Raj; KC, Sakar; Acharya, Sanjaya; Thapa, Rohit (Journal of Innovations in Engineering Education, 2026)
Chassis dynamometers are an essential tool for controllable and repeatable evaluation of vehicle performance. However, commercial chassis dynamometers are expensive and often inaccessible to small laboratories and educational institutions. In this regard, this study presents the development and experimental evaluation of an inertia-based chassis dynamometer for two-wheeler vehicles with continuously variable transmissions (CVTs), achieved at a cost of under 500. The system uses a roller flywheel assembly to simulate realistic drive-load conditions by translating the vehicle-rider translational inertia into an equivalent rotational inertia at the roller. Based on typical vehicle–rider mass characteristics of CVT scooters, a target system inertia of 1.80 kgm² was derived, while the fabricated assembly achieved 1.74 kgm². A Honda Dio (2015) was selected as the test vehicle based on availability, and its parameters fall within the intended design range. The brake power measurement at wheels was taken using a rope brake arrangement under steady-state conditions across a speed range of 0–41.55 km/h. Later, the results were validated against a commercial inertia dynamometer, which indicates that, although the fabricated dynamometer consistently underestimates brake power, both systems yielded similar power-speed trends with comparable linear slopes. And, the deviation between the datasets remained approximately constant across the speed range. Additionally, fuel economy measurements under inertia-only loading averaged at 35 km/l across urban speed ranges, approximately 13% below the real-world reported range of 40– 45 kmpl.